Interdependent action of KH domain proteins Krr1 and Dim2 drive the 40S platform assembly - Sturm, Miriam; Baßler, Jochen; Hurt, Ed (Nature Communications, 2017)
The biogenesis of eukaryotic ribosomes involves the coordinated interplay of a large number of assembly factors. Here, the authors detail how the conserved KH domain-containing assembly factors Dim2 and Krr1 function in ordering key events during ribosome maturation.